ANAK BERKEBUTUHAN KHUSUS DI SKH MADINAH SERANG BANTEN (DOWN SYNDROM: TUNAGRAHITA RINGAN) - Nada Tsana Fatinah; Yahdinil Firda Nadhira (STKIP Subang, 2024)
Down Syndrome is a disease caused by genetic abnormalities, due to abnormalities in chromosome development. In general, children with Down syndrome experience delays in all aspects of development, such as being slow to walk, fine motor development and language or speaking. Down syndrome is included in the group of mentally retarded, mentally retarded individuals who have intelligence that is significantly below average and is accompanied by disabilities and delays in physical and mental aspects during development. The aim of this research is to find out the condition of children with Down syndrome in the mild intellectual disability category at SKH Madinah Serang Banten. The research method used is qualitative with a descriptive approach. This research examines in more depth the phenomena that are the object of research. The results obtained were that the research subjects had delays in all aspects of their development such as walking, fine motor skills, language or speaking.